Ventricular resynchronization through biventricular cardiac pacing for the treatment of refractory heart failure in dilated cardiomyopathy - Galvão Fº,Silas S. (2002)
OBJECTIVE: The biventricular pacing (BVP) approach has good results in the treatment of congestive heart failure (CHF) in patients (pts) with disorders of intraventricular conduction. METHODS: We have applied BVP to 28 pts, with left ventricular pacing using minitoracotomy in 3 pts and the transvenous aproach via coronary sinus in 25 pts. The mean duration of the QRS complexes was 187 ms, in the presence of the left branch block in 22 pts, and right branch block + divisional hemiblock in 6 pts. All pts had been considerated candidates to cardiac transplantation, and were under optimized drug therapy. Sixteen pts were in Functional Class (NYHA) IV, and 12 in class III. The ejection fraction varied from 22 to 46% (average = 34%). The pacing mode employed was biventricular triple-chamber in 22 pts, and bi-ventricular dual-chamber in 6 pts (one with ICD). RESULTS: The pts were followed up for a period that ranged from 10 days to 14 months (mean 5 months). All pts presented clinical improvement after implant, chaging the NYHA Functional Class at the end of follow-up to Class I (9pts), Class II (10 pts) and Class III (6 pts). The initial mean ejection fraction have-raised to 37%. Two pts died suddenly. One patient died due to a pulmonary fungal infection. CONCLUSION: Ventricular resynchronization through BVP, improved significantly the Functional Class and, therefore, the quality of life. Assessments of myocardial function acutely performed do not reflect the clinical improvement observed.